The Influence of Organizational Culture and Work Ethics on Employee Performance at Sendy's Supermarket, Palangka Raya City, Central Kalimantan, Indonesia - Usup Riassy Christa (Formosa Journal of Applied Sciences, 2023)
Research on organizational culture related to the performance of self-service employees is very important in maintaining consumer trust. The research objective is to improve employee performance with work ethics contained in standard operating procedures. The research was conducted at a sendys supermarket in Palangka Raya, Central Kalimantan, Indonesia, by testing a questionnaire on 30 employees. Quantitative research methodology and analyzed with SPSS version 23. The results show that the very important role of organizational culture and work ethics is 73%. Important research implications are organized and work supervision from reports given by employees to leaders which contain organizational culture and work ethics, so that businesses can be sustainable in providing excellent service. Future research can be a reference in the field of human resources.